Understanding Z Generation Students’ Perceptions: Unpacking The Factors Behind Aversion to Learn English - Subarjo; Heriyawati, Dwi Fita; Karimullah, Imam Wahyudi (Universitas Cokroaminoto Palopo, 2025)
The research aims to identify both internal and external factors affecting students' motivation while proposing innovative solutions to enhance their engagement. The study employs a qualitative exploratory approach, utilizing semi-structured interviews and classroom observations to collect data from eleventh-grade students at an Islamic senior high school in Malang, Indonesia. Thematic analysis is used to examine patterns in students' responses, focusing on elements such as anxiety, teaching strategies, and environmental influences. Findings reveal that students’ reluctance stems from multiple factors, including fear of making mistakes, lack of material relevance, monotonous teaching approaches, and limited external support from peers and family. Additionally, technological integration and an engaging classroom atmosphere play a crucial role in shaping students’ motivation. To address these challenges, the study recommends incorporating interactive teaching methods, gamification, and contextual learning strategies. Strengthening teacher-student relationships and introducing ice-breaking activities at the beginning of lessons can help reduce anxiety and foster a more inclusive learning environment. The study concludes that enhancing students' motivation requires a holistic approach, combining pedagogical innovations, supportive learning environments, and family engagement. By implementing these strategies, educators can transform English learning into a more interactive and meaningful experience, ensuring students develop confidence and enthusiasm in mastering the language.